Synthesis of trifluoromethylthiolated pyridinones through the copper-mediated trifluoromethylthiolation of iodopyridinones. Issue 36 (26th August 2016) - Luo, Beibei; Zhang, Yunxiao; You, Yi; Weng, Zhiqiang
Abstract : A simple method for the synthesis of trifluoromethylthiolated pyridinones through the copper-mediated trifluoromethylthiolation of iodopyridinones was developed. Abstract : An operationally simple method for the copper-mediated trifluoromethylthiolation of iodopyridinones employing (bpy)CuSCF3 (1 ; bpy = 2, 2′-bipyridine) as a trifluoromethylthiolating reagent is presented. Various types of iodopyridinones are applicable and the trifluoromethylthiolated pyridinones are obtained in moderate to excellent yields. This method tolerates a variety of protecting groups on the nitrogen atom of pyridinones. In addition, scalability of the reaction is demonstrated.